Management skills: The importance of academic training for entrepreneurs in micro, small and medium-sized enterprises - Cirillo, Emilio Michele; Noro, Jorge Eduardo; Neto, João Pinheiro de Barros (Seven Editora, 2023)
The objective of this study was to verify the correlation between academic training and the success of entrepreneurs and managers in the administration of micro, small, and medium-sized enterprises (SMEs), seeking to highlight the skills that influence the positive results of these enterprises. To theoretically support the study, bibliographical research was carried out on education and managerial skills (knowledge, skills, and attitudes) necessary for entrepreneurs and managers to manage their businesses. A survey was applied to a random sample stratified by sectors (Construction, Industry, Commerce, Services, Agriculture) and size made up of 391 companies active in the state of São Paulo, Brazil, with a confidence margin of 95%, collecting the perception of entrepreneurs or senior executives, to verify the importance they attach to academic training and managerial skills in conducting and continuing their businesses. Among the results, when analyzing the average (p = 0.538), it was shown that university education alone is not considered a determining factor for the success of SMEs. However, the general assessment allows us to conclude that the maintenance of micro, small, and medium-sized companies in the market, their progress and evolution are related to the level of education and development of skills of entrepreneurs and managers involved in business administration, pointing out They emphasize that adequate training and continuing education processes focused on managerial skills are factors that positively influence the success of companies. A limitation of the study is the geographical limitation to a specific region of Brazil, for which new studies are suggested in other regions of the country. DOI:https://doi.org/10.56238/ptoketheeducati-055